Indigenous Production of Bovine/Bubaline Reproductive Hormones - Muralidhar, Kambadur (Journal of Buffalo Science, 2013)
The research work of our laboratory on buffalo pituitary hormones is summarized here in the context of MOET programme of our country. All the anterior pituitary protein hormones of this species (i.e. Follicle stimulating hormone (FSH), Growth Hormone (GH) and others) have been purified from freshly frozen pituitaries. These hormones have been extensively characterized with regard to physico chemical, immunochemical and biological features. We have also produced buffalo Prolactin (PRL), Luteinizing Hormone (LH), FSH and Thyroid Stimulating Hormone (TSH) by recombinant DNA techniques.